From adoption to implementation? An academic perspective on Sustainable Fisheries Management in a developing country. (December 2015) - Espinoza-Tenorio, Alejandro; Espejel, Ileana; Wolff, Matthias
Abstract: Despite the fact that Sustainable Fisheries Management (SFM) has long been proposed internationally, it remains controversial. Practical and successful applications are scarce, especially in developing countries with a recent history of massive overfishing, such as Mexico. Although SFM has been adopted at the highest level of the Mexican legal framework during the last two decades, its successful implementation still faces a series of complex challenges. At present, important changes in the Mexican political regime are at a breaking point, motivating the academic discussion about the national implications of adopting SFM approaches. Through the analysis of a series of deep interviews of key actors, combined with published material, the article illustrates how the fast-track adoption of SFM approaches has fared in a national fisheries context, the current situation being largely dysfunctional with regard to the challenges of SFM. A complicated mixture between unbeaten management and academic vestiges caused the present circumstances of an enhanced but limited fisheries system. The article proposes academic initiatives required to improve the implementation of SFM in Mexico based on an enhanced understanding of domestic historic conditions and challenges. Highlights: Advances in SFM in Mexico are superficial because vices persist from the old system. In Mexico SFM objectives are often overruled by short-term socioeconomic needs. SFM implementation implies strategic planning based in local and historical context.